Implementasi Naive Bayes Untuk Klasifikasi kinerja Guru Pada Sekolah Dasar Kristen Aletheia - Akhmad Budi (Jurnal Informatika dan Bisnis, 2013)
Quality of human resources plays an important roles when building a great nation, the higher quality of human resources reflect the higher quality of whole nation. Many factors affect the life of nation and state, one of those factors is education. School as a foundation place to create educational environment plays a huge roles as an asset to improve the quality of knowledge. Aletheia Primary School established to answer the absence of importance for educational world at the primary stage. With the vision to be the christian institution that commited to create student that have a knowledge base of the truth. Aletheia Primary School got a purpose to analyze teacher’s performance to help school create a future planning. But, data to be used still need a deep processing until they become a reference in making a decision. This research used Classification Data Mining technique with Naive Bayes